An electrospun micro/nanofibrous mesh based nontoxic sensor for optical detection of high humidity1. Issue 9 (7th May 2015) - Wang, Tianyu; Fu, Hongxia; Duan, Xinrui; Li, Zhengping
<x xml:space="preserve">Abstract</x> Optical transition of a polyethylene oxide electrospun micro/nanofibrous mesh from opaque to transparent for low toxicity and irreversible humidity monitoring.